2020
DOI: 10.3390/insects11070419
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antioxidant Enzymes Activity and Metabolomic Profiles in the Guts of Honey Bee (Apis mellifera) Larvae Infected with Ascosphaera apis

Abstract: The fungus Ascosphaera apis, an obligate fungal pathogen of honey bee brood, causes chalkbrood disease in honey bee larvae worldwide. Biological characteristics of the fungal pathogen and the molecular interactions between A. apis and honey bees have been studied extensively. However, little is known about the effects of A. apis infection on antioxidant enzyme activities and metabolic profiles of the gut of honey bee larvae. In this study, sandwich enzyme-linked immunosorbent assay and LC-MS based unta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…Even during the excessive proliferation of pathogens, the intestinal epithelium produces and releases high levels of ROS, causing significant oxidative stress [ 111 , 112 , 113 ]. Li et al [ 4 ] recently reported that A. apis infection induced oxidative stress in honeybee larvae, and decreased levels of the metabolites involved in combating oxidative stress could compromise the antioxidant defenses of the infected larvae. The specific activities of antioxidant enzymes (CAT, GST and SOD) and the levels of metabolites (taurine, docosahexaenoic acid and l -carnitine) involved in combating oxidative stress were significantly decreased in the guts of infected honeybee larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even during the excessive proliferation of pathogens, the intestinal epithelium produces and releases high levels of ROS, causing significant oxidative stress [ 111 , 112 , 113 ]. Li et al [ 4 ] recently reported that A. apis infection induced oxidative stress in honeybee larvae, and decreased levels of the metabolites involved in combating oxidative stress could compromise the antioxidant defenses of the infected larvae. The specific activities of antioxidant enzymes (CAT, GST and SOD) and the levels of metabolites (taurine, docosahexaenoic acid and l -carnitine) involved in combating oxidative stress were significantly decreased in the guts of infected honeybee larvae.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is economically important since it results in significant losses of both honeybees (under certain circumstances, it can kill colonies) and colony productivity [ 2 ], and indications suggest that its incidence may be increasing [ 3 ]. Recent research demonstrated that A. apis infection, together with other biotic and abiotic factors, induces oxidative stress and impairs the antioxidant defensive capacity of honeybee larvae [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The movement of managed honey bee colonies across different agricultural landscapes and the location of colonies inside greenhouses impact on the levels of oxidative stress (Morimoto et al 2011;Simone-Finstrom et al 2016). Moreover, flight activity, invasive predator species, and pathogens in hives as well as pesticides used for pest control in numerous crops disturb the honey bee oxidative homeostasis (Balieira et al 2018;Gregorc et al 2018;Margotta et al 2018;Leza et al 2019;Li et al 2020). Oxidative stress has been suggested to lead to damage in insects exposed to low temperatures (Lalouette et al 2011;Kojić et al 2019;Tawfik et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research demonstrated that several biotic and abiotic factors, induce oxidative stress and impair the antioxidant defensive capacity of honey bee larvae [ 9 , 157 , 158 , 159 , 160 ].…”
Section: Functional Properties Of Labmentioning
confidence: 99%